Cif sales terms as a mean to derive additional competitive advantage – perspective from a trader focusing on commodity requiring mr tanker tonnage - Liu, Ziqi (2018)
A trader who sells on CIF sales terms is obligated to arrange the transportation and cover for insurance. This means that traders are exposed to the fluctuation of the freight rate which could be an opportunity to generate additional profit or a threat to make a loss. Therefore, to determine whether employing CIF sales term is a strategy that helps traders gain competitive advantage or a strategy that causes them to lose out, risk and return of the strategy are examined in this research. In volume one, trader acquires tonnage from the spot market and he is exposed to the freight rate risk. In volume two, this freight risk is minimized by having control of the tonnage through time-chartered vessels as well as ownership of the vessels. However, the trader is exposed to the market risk of fluctuating operating costs which mainly consists of bunker costs. In both volumes, it is found that traders can earn profit from the strategy of employing CIF sales term. In this volume, the option of joint venture (JV) between traders and ship owners is explored as an alternative to reduce risk exposure of both parties since both pull resources together to share the risks and returns. A quantitative experiment is conducted whereby Return on Invested Capital (ROIC) and Coefficient of Variation (CV) are calculated to determine the return and risk of the JV respectively. The calculated ROIC and CV are then compared with results from volume one and two for trader and external benchmark for shipowner. It is found that through forming a JV, both trader and shipowner are able to reduce their risks and, in some cases, the profit/loss of trader and shipowner is better off than if they operate independently because profit/loss are shared between the partners of a JV.